Identification of 3 new pleotropic loci conferring resistance to Leaf Rust and Yellow Rust in wheat on chromosome 2A in "Borlaug 100", Mucy and Mukoe - CGIAR Research Program on Wheat (2021)
The genomic region is identified with flanking markers and KASP marker development is underway